Математическое описание вибрационного процесса клапанного механизма ГРМ ДВС и его моделирование на базе электромеханических аналогий - Лавриненко, Ольга Валериевна (НТУ "ХПИ", 2016)
В работе дается математическое описание вибрационного процесса клапанного механизма двигателя внутреннего сгорания (ДВС) и моделируются его вибрации, которые рассматриваются как аналог тока в активно-индуктивно-емкостной цепи во время колебательного переходного процесса. Параметры такой цепи соответствуют определенным параметрам механической системы. Показано, что информативными параметрами для диагностики клапанов двигателя могут быть коэффициент затухания тока и его величина, значения начальных и центральных моментов распределения максимумов тока и характер функции распределения вероятностей.

Technical perfection of internal combustion engines place increasing demands, including the reliability during operation. Diagnostics of technical condition of an effective way to ensure the reliability of the engine and its main systems and mechanisms. The gas distribution gear - one of the main mechanisms of the engine, the parameters which vary during operation. We give a mathematical description of the vibratory process valve internal combustion engine mechanism, modeled its vibrations, which are considered as an analogue of the current in the active-inductive-capacitive circuit during the vibration transition. The parameters of this circuit correspond to certain parameters of the mechanical system. It is shown that the informative parameters for the diagnosis of the engine valve can be rate of current decay and its value, the value of the initial and central moments of the distribution of current peaks and the nature of the probability distribution function.
The mathematical description of the vibratory process valve timing mechanism of ICE and its simulation based on electromechanical analogies
Keywords: двигатель внутреннего сгорания; газораспределительный механизм; диагностика; информативный параметр; коэффициент затухания; internal combustion engine; gas distribution mechanism; damping coefficient